ORIENTASI BUDAYA ANAK KAWIN CAMPUR ANTARA ETNIS MELAYU DAN MADURA DI KECAMATAN TANGARAN - Nasoba, Nasoba; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This research aims to describe the cultural orientation of mixed marriage from the aspects of language, kinship, and religion. The method applied in the study is descriptive in the form of qualitative research. The data resource in this study is a couple from the mixed marriage between Malay and Madurese in Tangaran District of Sambas Regency. The data were collected through observation, interview, and documentation technique. Based on the analysis, the language used in daily communication is Sambas Malay that it is the language used by Malay ethnicity. The kinship tends to be closer to the family of the Sambas Malay ethnic group. This can be seen from the use of nicknames originating from ethnic Malays. From the religious aspect, it tends to be oriented towards the Malay ethnic culture. Those from Madura have experienced adjustments to the Sambas Malay ethnic group because they live in the village where the majority of the population are ethnic Malays. Henceforward, it is concluded that the cultural orientation from the results of mixed marriage from aspects of language, kinship, and religion are generally oriented to Malay ethnicity. Â Keywords: Culture, Mixed Marriage, Orientation Â